THE FORMATION OF THE COHERENT SPEECH OF JUNIOR SCHOOLCHILDREN WITH INTELLECTUAL DISABILITIES BY MEANS OF ANIMATION-BASED THERAPY - Arkhipova, Svetlana; Grishina, Olga; Minaevа, Natalia; Mikheikinа, Tatiana; Ryabova, (Revista Inclusiones, 2019)
The article deals with the problem of the formation of coherent speech of junior schoolchildren with intellectual disabilities affecting the education, development, and socialization of children of this category, and requiring the use of not only conventional but also nontraditional means, of which one is cartoon based or animation-based therapy. The aim of the study is to develop organizational and methodological foundations for the formation of coherent speech of junior schoolchildren with intellectual disabilities by means of animation-based therapy. The study was based on general scientific methods of cognition, such as analysis, synthesis, comparison, generalization; as well as a pedagogical experiment (ascertaining, forming, and control), as well as analysis of empirical data. Methods of mathematical statistics in Excel were used to process the research data. The conducted study allowed tracing the positive dynamics in the formation of coherent speech of junior schoolchildren with intellectual disabilities before and after the experimental work based on the use of animation therapy. The obtained data confirm that the specially organized work within the Young Director children's animation studio effectively contributes to the level of formation of coherent speech of junior schoolchildren with intellectual disabilities by forming a culture of speech; expanding and refining their vocabulary; improving the structure of the sentence; developing the skill of coherent speech based on the demonstration of actions and without visual support; enriching monologic and dialogic forms of speech; as well as contributing to emergence of motivation in communication with peers and adults in the course of creating cartoons. The materials of the article can be useful for specialists and teachers of educational organizations interested in the formation of coherent speech of junior schoolchildren with intellectual disabilities by means of animation-based therapy.